Penerapan Metode Bermain Peran untuk Meningkatkan Prestasi Belajar Siswa dalam Pembelajaran Adab Bergaul dengan Saudara dan Teman - Munawar, Defi (Ali Muchasan, 2017)
Akidah Akhlak is one aspect of the scope of Islamic religious education (PAI) is very important for the life of nation, state, and religion, because Akidah Akhlak is a basic lesson that must be learned by learners, to know that behavior is very influential for his life, especially on learning manners mingle with relatives and friends. In learning morals associate with siblings and friends learners have difficulty to master the lesson, because the monotonous learning process using lecture method resulted in the concentration of learners decreased. So it takes a method that can trigger the spirit of students to be able to achieve learning objectives, and can achieve maximum learning achievement. While the purpose of this study is to find out how the application of role playing methods in improving learning achievement on learning adab hanging out with relatives and friends class VIII A Junior High school of Islamic Manba'ul Ulum Jatirejo Damarwulan Kepung Kediri.